THE OVERCOME OF STUDENTS’ LEARNING DIFFICULTIES OF ARABIC SPEAKING AND WRITING SKILLS BASED ON EDWIN GUTHRIE’S THEORY - Basid, Abdul; Erwhintiana, Ifi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This research aims to describe the causal factors of learning difficulties of students’ speaking and writing skills in ArabicLanguage and Literature Department and to find the solutions in overcoming of learning difficulties of students’ speaking and writing skills in Arabic Language and Literature Department based on Edwin R. Guthrie perspective. This research is descriptive qualitative research. This research is also a case study. The subjects of this research are students of ArabicLanguange and Literature Department at Humanity Faculty in UIN Maulana Malik Ibrahim academic year 2017. The techniques of data collections that used in this research are observation, documentations, and interviews. The techniques of data validation used are increasing theperseverance, applying triangulation, and discussing with the experts. Then, the technique of data analysis used is Miles and Huberman model that contains of three steps. They are data reduction, data presentation, and data verification. The result of this research shows that: (1) the causal factors of learning difficulties of students’ speaking and writing skills in ArabicLanguage And Literature Department are instrinsic and extrinsic aspects, as follow: (a) the instrinsic aspects that cause the difficulties in speaking skills are lack of mastering vocabularies, lack of matering grammatical in nahwu and shorof, lack of time management, the difficulty of learning methods. Thus far,the extrinsic aspects that cause the difficulties in speaking skills are the lack of habituation to practice talking with classmates; (b) the instrinsic aspects that cause the difficulties in writing skills are lack of mastering vocabularies, lack of mastering grammatical (nahwu and shorof), lack of understanding imla’ correctly. Thus far, the extrinsic aspects that cause the difficulties in writing skills are unproper learning strategy; (2) thesolutions in overcoming of learning difficulties of students’ speaking and writing skills in ArabicLanguage and Literature Department based on Edwin R. Guthrie perspectiveare: (a) the solutions for the difficulties in speaking skills are memorizing and using vocabularies, and establishing language area; (b) the solutions for the difficulties in writing skills are starting writing a vocabulary, a sentence, a paragraph and applying a creative learning strategy, such writing a diary, poster, and daily report.